Comparison of psychological skill characteristics of male and female karate athletes at the 19th Asian Games in 2023 in Hangzhou, China - Pulungan, K. A.; Kristiyanto, A.; Setyawati, H.; Sulaiman; Haryani, M.; Kadir, S. S. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2026)
Background. Research on the psychological skills of players, based on a gender perspective is still limited, especially in elite karate athletes.